Behavioural ethogram to inform ex-situ initiatives for a critically endangered bird – the case of the Plains-wanderer - Van Sluys, Monique; Pauligk, Yvette; Burns, Alicia; O’Riordan, Mark; Matkovics, Richard; Hartnett, Chris; Pitcher, Benjamin J. (Frontiers in Conservation Science, 2024)
A thorough understanding of behaviour is essential to a species recovery effort, not only to inform management and husbandry decisions, but critically, to ensure optimum survival of released animals and their offspring. The endangered Plains-wanderer, endemic to Australia and the only extant member of its family, is a bird of great conservation significance. Despite their phylogenetic uniqueness and conservation status, very little is known about their basic behavioural ecology. As part of the National Recovery efforts, an ex-situ breeding program was established to create an insurance population with the aim of releasing zoo-bred birds into their natural range. Such programs provide unique opportunities to conduct detailed behavioural and ecological studies.However, such studies are dependent on a comprehensive understanding of basic behaviour and associated social interactions, as well as a common vocabulary across institutions when it comes to describing patterns of behaviour. Therefore, a detailed ethogram is a vital first step. Here we have collated initial behavioural observations and descriptions from three main breeding institutions to create a unified ethogram across sites, with the aim of facilitating future research endeavours.Ultimately a systematic understanding of behaviour will not only improve management and conservation initiatives, but also the understanding of adaptability to potential threats going forward.